A Dynamic Systems Framework for Gender/Sex Development: From Sensory Input in Infancy to Subjective Certainty in Toddlerhood - Fausto-Sterling, Anne (Frontiers in Human Neuroscience, 2021)
Between the ages of six to eight months infants evidence the ability to distinguish between male and female voices. By nine months they can differentiate male from female faces. Between 18 and 24 months the ability to distinguish adult males from adult females transforms into the ability to recognize gender/sex-stereotyped activities. Finally, between 24 and 36 months, as a behavioral expression of their own emerging subjective sense of gender/sex, toddlers begin to voice gender/sex-stereotyped preferences for clothing, color, toys and playmates. In this Theory and Hypothesis article I posit that, from birth to 15 months, infants and caregivers partake of dyadic interactions which, through repetition, imbue the infant with an embodied understanding of gender/sex. During this developmental period gender/sex is primarily an intersubjective project. From 15-18 months there are few reports of newly-appearing gender/sex differences, and I hypothesize that this absence reflects a period of instability during which there is a transition from gender/sex as primarily inter-subjective to gender/sex as primarily subjective. Beginning at 18 months, a toddler’s subjective sense of self as having a gender/sex emerges, and it solidifies by three years of age. I propose a dynamic systems perspective to track how infants first assimilate gender/sex information during the intersubjective period (birth to 15 months); then explore what changes might occur during a hypothesized phase transition (15 to 18 months), and finally, review the emergence and initial stabilization of individual subjectivity–the period from 18 to 36 months. The critical questions explored focus on how to model and translate data from very different experimental disciplines, especially neuroscience, physiology, developmental psychology and cognitive development. I close by exploring a research consortium on gender/sex development during the first three years after birth.